Optimal design of intelligent sensors in improving the safety of steel structures - Khiali, Vahid; Oyarhossein, Mohammad Amin (Technium Sustainability, 2023)
Instrument health monitoring can identify the behavioral characteristics and detect the possible failure of structures during their lifetime. Structural health monitoring is a process in which various issues are addressed, including the diagnosis and location of damage to structures. A structural health monitoring system receives information about the instrument's behavior from the sensor network. Because installing sensors, receiving information from them, recording and processing data, and concluding is an essential process in monitoring, lack of data leads to incorrect or insufficient results, and additional data confuses the analysis. And data processing. Also, increasing the number of sensors increases the cost of monitoring the structure. Therefore, the optimal design of the sensors network to correctly use sensors in terms of type, number, and critical location is essential.